Preliminary population studies of the grassland swallowtail butterfly Euryades corethrus (Lepidoptera, Papilionidae) - Atencio, Guilherme (2023)
Funding Information: This article is a chapter of the PhD thesis of the first author. We would like to thank Dr. Vera Lúcia da Silva Valente Gayeski for allowing us to use the Drosophila lab and all its equipment to perform the wetlab experiments, as well as supporting us in all stages of this work. Grant sponsor: Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq); Brazil. Grant number: 163268/2015-0.